Progressive Discipline: An Oxymoron? - Eden, Geneviève (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
This paper contrasts competing paradigms of a key issue in the employee-employer relationship: the application of the concept of progressive discipline. In a review of both the arbitral jurisprudence in the unionized sector, and the organizational behavior literature, the author illustrates two very different perspectives regarding the application of discipline in the workplace: one view is embodied in arbitral law and focuses on the corrective effects of discipline, while the other is embodied in behavior modification theory and emphasizes its negative effects. The notion of discipline is then discussed in a broader perspective by highlighting some current trends in human resource management, as well as alternative approaches to dealing with employee misconduct.